(untitled) (Journal of Universal Excellence, 2026)
Research Question: The article analyses the importance of human capital and dimensions of organizational climate (internal relations; delegating leadership; organisational loyalty; career development; employee satisfaction and rewards; professional training and education) in the case of the Slovenian Tourist Agencies (TA). Purpose: To examine the importance of human capital and dimensions of organizational climate in TA and through a questionnaire carry out a quantitative research in Slovenian TA. Method: The collected survey data are analysed by the following statistical methods: descriptive analysis, factor analysis and principal component analysis, multiple regression analysis and structural equation methods. Results: There is a positive correlation between human capital and dimensions of the organizational climate in TA. This does not hold for delegating leadership as a component of organizational climate. Organization: Managers need to give a greater attention to delegating leadership as a dimension of organizational climate. Society: To inform the owners, managers and heads of TA as well as other employees that the organizational climate is important for all stakeholders and that it is necessary to highlight its increasing importance. Originality: It is the first such study in Slovenia and one of the first in the world literature. Limitations / further research: The questionnaire was aimed at owners / managers / heads and other employees in the TA and their branches, but not to their business partners who contribute greatly to quality of services in TA. Suggestions for further explorations are the longitudinal research or inclusion of other countries and comparing the data.